Towards a comprehensive model for the positive electrode system of a lead-acid traction cell : a thesis presented in partial fulfilment of the requirements for the degree of Doctor of Philosophy in Production Technology at Massey University - Nilson, Ross Richard (Massey University, 1989)
This thesis develops a detailed model for the positive electrode system of an industrial lead-acid traction cell. This is referred to as the VIAM model since it relates the positive electrode voltage (V) and cell current (I) to internal distributions of current, potential, acid concentration and active mass (AM). The model can simulate both discharge and charge for a wide range of practical currents. The model takes account of microstructure, macrostructure and non-reactive structure in the positive active mas (AM). It also takes account of other cell components that affect the supply of acid to the positive electrode. The model has direct application to fundamental cell design (for example AM development) and cell systems design (for example cell charger design). The model is based on established experimental studies, theories of electro chemical interface reactions and theories of ionic transport in electrolyte solution. From this base, three elemental models and an aggregate model are developed. The elemental models represent details of the microstructure of the positive electrode AM. The aggregate model represents the electrolyte mass (acid) and charge transport system within the positive electrode and other cell components. The combination of the elemental and aggregate models make up the VIAM model. The performance of the VIAM model (and underlying models) is assessed by comparing model results with findings from experimental studies in the literature. In addition, experiments undertaken as part of this work are used to test the model. The model and experimental results are in close agreement.
Keywords: Electric batteries; Models